PENGEMBANGAN KURIKULUM MUATAN LOKAL DALAM MEMBENTUK KARAKTER LULUSAN SISWA SMA 2 DARUL ULUM REJOSO JOMBANG - Syukrianto Syukrianto (Universitas Islam Madura, 2019)
Curriculum development of local content developed with the development of the theory and practice of education, also varies according to the flow or educational theories which adhered. Strengthening local content curriculum developed by SMA 2 Darul Ulum Rejoso Jombang pesantren with in the school curriculum of reinforcement for the creation of local content. This research method using of development Dick & Carey (2009), is the identification of the learning objectives, analysis of learning, learner and context analysis, define learning objectives, development assessment instruments, developing learning strategies, developing and selecting study materials, design and conduct formative evaluation, revision and designing and conducting evaluation summative. This research data using the local content curriculum development for SMA 2. The result and discusion concept of strengthening the curriculum of SMA 2 educational concept is Tebuireng reforming education boarding school that has existed previously with the emphasis on the concept of making the Qur'an as the main source for research in learning and make the Quran as development of an strengthening local charge. The formation of character in students graduate SMA 2 is able to master the three curriculum i.e. boarding schools curriculum, national curriculum and curriculum of Cambridge, formally pocketed three diplomas i.e. diploma boarding schools, national public ijasah, and Cambridge Certificate, which will be used as a provision for continuing education to the next level.